Improvement in both severe obsessive–compulsive disorder and refractory tardive dystonia following electroconvulsive therapy: A case report. Issue 2 (31st May 2022) - Mihara, Yasuha; Otsuki, Koji; Hayashi, Mai; Yamashita, Satoko; Nagahama, Michiharu; Hayashida, Maiko; Wake, Rei; Hashioka, Sadayuki; Abe, Satoshi; Inagaki, Masatoshi
Abstract: Background: Obsessive–compulsive disorder (OCD) is often resistant to treatment and may be complicated by tardive dystonia (TDt) with the use of neuroleptics. Furthermore, patients with TDt often have an inadequate response to pharmacotherapy. Although electroconvulsive therapy (ECT) is considered a common treatment option for both TDt and OCD, its efficacy has not been well established for either condition. Case Presentation: Our case was a 37‐year‐old Japanese woman who showed improvement in both refractory TDt and severe OCD following ECT. A total of 12 ECT sessions resulted in an improvement in both diseases. To the best of our knowledge, this is the first report of a case in which ECT was effective for both TDt and OCD. Conclusion: Our report highlights the following two points: when TDt is associated with severe OCD, and the effect of pharmacotherapy is inadequate, ECT may be considered as a treatment option; given the common mechanism of frontal cortex‐basal dysfunction reported in both dystonia and OCD, ECT may have an effect on this pathway.